Critical Assessment of Banking Institutions in South Africa - Fotso, Bakam; Edoun, E. I (Journal of Economics and Behavioral Studies, 2017)
Banks play an important role in a countryâ€™s economy through investments, deposits and withdrawals. Many banking products are sold to clients to meet their financial needs and obligations. Their performances are therefore very critical in supporting socio economic development. Financial institutions still facing challenges linked to the lack of financial previsions through the use of financial tool that allows preventing financial distress. Banks are not always well-managed because managers lack capacity and the sound knowledge in dealing effectively with the analysis of risk and return and decision-making. The current study highlights and gives orientations on key performance indicators that bank can use to manage their financial conditions in advance in a sustainable manner. The major objective of this research is to critically assess the South African banks performance using Financial Ratio Analysis (FRA)and descriptive statistics through comparative financial statement analysis form 2010 to 2013 betweenâ€œ the big fourâ€ South African banks. In using correlational analysis, the study aim to establish the link between exogenous and endogenous variables of bank performance. The results showed that FirstRand bank was the best achiever with a higher level of performance following by Standard bank, then Absa and Nedbank. Furthermore, it appears that there is a strong relationship between bank performance and bank size because the volume of assets represents the bigger source of bank incomes. This study opens door to further study including both large and small banks and a comparative analysis between two research methods. The paper is divided into five major sections.